Time for curriculum reform: the case of mathematics - Noyes, Andrew; Wake, Geoffrey; Drake, Pat (Taylor and Francis Group, 2013)
Mathematics education is rarely out of the policy spotlight in England. Over the last ten years, considerable attention has been given to improving 14-19 mathematics curriculum pathways. In this paper we consider some of the challenges of enacting curriculum change by drawing upon evidence from our evaluation of the Mathematics Pathways Project. From 2004-10 this project, which was directed by England’s Qualifications and Curriculum Authority, aimed to improve the engagement, attainment and participation rates of 14-19 year old learners of mathematics. Our particular focus is upon the temporal problems of piloting new curriculum and assessment and we draw on Lemke’s discussion of time-scales, heterochrony and the adiabatic principle to consider the interlocking and interference of various change processes.